Impact of Antiretroviral Treatment Containing Tenofovir Difumarate on the Telomere Length of Aviremic HIV-Infected Patients. (1st September 2017) - Montejano, Rocio; Stella-Ascariz, Natalia; Monge, Susana; Bernardino, José I.; Pérez-Valero, Ignacio; Montes, María L.; Valencia, Eulalia; Martín-Carbonero, Luz; Moreno, Victoria; González-García, Juan; Arnalich, Francisco; Mingorance, Jesús; et al.
Abstract : Objective: To evaluate the in vivo relevance of the inhibitory effect of tenofovir on telomerase activity observed in vitro. Design: Cross-sectional study of HIV-infected patients with suppressed virological replication (HIV RNA <50 copies/mL for more than 1 year). Methods: Telomere length in whole blood was measured by quantitative real-time polymerase chain reaction. We performed a multivariate analysis to elucidate variables associated with telomere length and also evaluated the association between telomere length and use of tenofovir difumarate (TDF) adjusted by significant confounders. Results: 200 patients included, 72% men, median age 49 (IQR 45–54.5), 103 with exposure to a TDF containing antiretroviral treatment (ART) regimen (69.9% for more than 5 years) and 97 never exposed to a TDF containing ART regimen. In the multivariate analysis, significant predictors of shorter telomere length were older age ( P = 0.008), parental age at birth ( P = 0.038), white race ( P = 0.048), and longer time of known HIV infection (10–20 and ≥20 years compared with <10 years, P = 0.003 and P = 0.056, respectively). There was no association between TDF exposure and telomere length after adjusting for possible confounding factors (age, parental age at birth, race, and time of HIV infection). Total time receiving ART and duration of treatment with nucleoside reverse transcriptase inhibitors were associated with shorter telomere length, but these associations were explained by time of known HIV infection. Conclusions: Our data do not suggest that telomerase activity inhibition caused by TDF in vitro leads to telomere shortening in peripheral blood of HIV-infected patients. Abstract : Supplemental Digital Content is Available in the Text.